1999
DOI: 10.1016/s0550-3213(99)00046-2
|View full text |Cite
|
Sign up to set email alerts
|

Self-dual effective action of N = 4 super-Yang-Mills

Abstract: The full low energy effective action of N = 4 SYM is believed to be self-dual. Starting with the first two leading terms in a momentum expansion of this effective action, we perform a duality transformation and find the conditions for self-duality. These determine some of the higher order terms. We compare the effective action of N = 4 SYM with the probe-source description of type II B D3-branes in the AdS 5 × S 5 background. We find agreement up to six derivative terms if we identify the separation of the 3-b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
149
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(153 citation statements)
references
References 36 publications
4
149
0
Order By: Relevance
“…As a matter of fact, if the conjecture is true it will actually circumvent the necessity of quantizing the string on a curved space, at least for the open string.) It is similar, in spirit, to what was shown in [19,20]. There it was shown that the effective action of N=4 SYM that contains quantum (and the non-perturbative ) corrections can be interpreted as a non-linear sigma type action with a curved target space.…”
Section: Anticipated Mechanism For Divergence Cancelationsupporting
confidence: 68%
“…As a matter of fact, if the conjecture is true it will actually circumvent the necessity of quantizing the string on a curved space, at least for the open string.) It is similar, in spirit, to what was shown in [19,20]. There it was shown that the effective action of N=4 SYM that contains quantum (and the non-perturbative ) corrections can be interpreted as a non-linear sigma type action with a curved target space.…”
Section: Anticipated Mechanism For Divergence Cancelationsupporting
confidence: 68%
“…We hope to obtain similar results for the M2-branes, and this is one of the main motivations for this paper. It may be noted that the HD corrections for four dimensional field theories with N = 1 supersymmetry have already been studied [15][16][17][18]. Such terms have also been studied using the four dimensional harmonic superspace [24][25][26][27].…”
Section: Jhep10(2015)002mentioning
confidence: 99%
“…Moreover, the non-holomorphic effective potential is found exactly up to coefficient and given by eq (7) [10]. Any perturbative or non-perturbative quantum corrections are included into a single constant c. However, this result immediately face the problems: 1) is there exist a calculational procedure allowing to derive H(W/Λ,W /Λ) in form (7) The answers all these questions have been given in [11][12][13][14][15][16][17]. Further we are going to discuss a general manifestly N =2 supersymmetric and gauge invariant procedure of deriving the non-holomorphic effective potential in one-loop approximation [13,16].…”
Section: General Form Of Non-holomorphic Effective Potentialmentioning
confidence: 99%